Gynodioecy in the common spindle tree (Euonymus europaeus L.) involves differences in the asymmetry of corolla shapes between sexually differentiated flowers - Neustupa, Jiri (PeerJ, 2020)
Gynodioecy is typically associated with a smaller perianth size in purely pistillate flowers than in hermaphrodite flowers. However, it is unclear whether this size differentiation is associated with any differences in flower shape between the two sexual groups. A geometric morphometric analysis of the symmetry of tetrameric corolla shapes was used in the study of Euonymus europaeus L., Darwin's classical system of floral sexual differentiation. I investigated whether there are any shape differences between the female and bisexual flowers, with respect to both purely symmetric variation involving coordinated shape changes of the four petals and asymmetry among petals within flowers. The corolla shapes of the female and bisexual flowers and the variability among flowers within each sexual group were very similar in the purely symmetric components of shape variation. However, the female flowers were significantly more asymmetric with respect to both the lateral and transversal asymmetry of their corolla shapes. This is the first study to apply geometric morphometrics in the analysis of morphological patterns in a sexually differentiated gynodioecious plant system. The results showed that subtle shape differences in corolla asymmetry differ between the sexual groups and indicate diverging developmental or selection signals between the sexes.
Keywords: Euonymus europaeus; Floral biology; Biradial symmetry; Actinomorphy; Gynodioecy; Geometric morphometrics